Pengaruh Kesenjangan Sosial dan Ketimpangan Ekonomi Terhadap Tingkat Kriminalitas di Indonesia - Aprilisa Faustine Kacaribu; Barika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to investigate the factors of social inequality and economic inequality that contribute to different crime rates in Indonesia from 2018 to 2022. In this research, variables such as poverty, unemployment, average years of schooling, population, and Gini ratio will be considered . This research uses quantitative methods to analyze panel data using multiple linear regression methods and Eviews 12. The results of the research show that the variables of population and poverty influence the crime rate in Indonesia, but the variables of unemployment, average years of schooling, and the Gini ratio do not influence the rate. crime in Indonesia.